2006
DOI: 10.1167/iovs.05-0971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Photoreceptors and Visual Function in Developing Zebrafish

Abstract: Ethanol affects photoreceptor function at low concentrations that do not disturb retinal morphology. Higher levels of ethanol inhibit photoreceptor development and cause hypoplasia of the optic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 45 publications
8
72
1
Order By: Relevance
“…In zebrafish, ethanol exposure to embryos results in phenotypes similar to those seen in other animal models, and in humans (Blader & Strahle, 1998;Bilotta et al, 2002Bilotta et al, , 2004Carvan et al, 2004;Arenzana et al, 2006;Matsui et al, 2006). Zebrafish embryos are semi-transparent and develop externally over a very short, and experimentally manipulable, period.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In zebrafish, ethanol exposure to embryos results in phenotypes similar to those seen in other animal models, and in humans (Blader & Strahle, 1998;Bilotta et al, 2002Bilotta et al, , 2004Carvan et al, 2004;Arenzana et al, 2006;Matsui et al, 2006). Zebrafish embryos are semi-transparent and develop externally over a very short, and experimentally manipulable, period.…”
Section: Introductionmentioning
confidence: 89%
“…Photoreceptor development is sensitive to ethanol exposure from 48 to 72 hpf (Matsui et al, 2006). To determine if ethanol exposure from 24 to 48 hpf affects subsequent photoreceptor differentiation, treated embryos were transferred to unmodified system water, and then processed at 72 hpf for indirect immunofluorescence using zpr1, an antibody that labels a cell-surface epitope on red/green double cones (Larison & Bremiller, 1990) and zpr3, an antibody that labels rod photoreceptors.…”
Section: Ethanol Exposure Affects Retinal Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in the eye movements indicated that acute ethanol treatment may impair the vision function in zebrafish larvae. 13,32 D. Analysis of cardiac function in response to ethanol treatment…”
Section: Ethanol-induced Behavioral Responses Of Zebrafishmentioning
confidence: 99%
“…10,11 For example, it was reported that acute ethanol treatment could adversely affect neural development. 12,13 Ethanol exposure has also been shown to influence the histaminergic and dopaminergic systems and to stimulate the locomotion in larval zebrafish. 2,14 However, little has been done to associatively study ethanol-induced acute responses in different organ systems, and to simultaneously address brain and cardiac physiology with direct links to behavioral alternations, mainly due to the lack of technology that can perform behavioral study and cellular imaging in an integrated format.…”
Section: Introductionmentioning
confidence: 99%